Analisis Feminisme Radikal terhadap Ketidakadilan Gender pada Tokoh Ibu dan Anak dalam Film “Andai Ibu Tidak Menikah dengan Ayah” Kajian Kate Millett (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the forms of gender injustice experienced by the mother and daughter characters in the film If Mother Didn't Marry Father using radical feminism studies. This study uses a qualitative approach with descriptive analysis methods. The research data consists of dialogue, scenes, and character behavior that indicate gender injustice in the film. The analysis was conducted using the theory of radical feminism proposed by Kate Millett which emphasizes criticism of the patriarchal system in social life. The results of the study show that the mother and daughter characters in the film experience various forms of gender injustice, such as subordination, marginalization, and restrictions on freedom in determining life choices. These conditions arise due to the strong influence of the patriarchal system in the family that places men as the party with greater power. Through this film, it can be seen that power relations within the family play a major role in shaping the gender injustice experienced by women. This study is expected to provide an understanding of how film media represents the issue of gender injustice in family life.